Dynastic Loyalism, Morality and Family Values among Romanians in Transylvania during the First World War - TURCU, Lucian (Studia Universitatis Babeș-Bolyai Historia, 2018)
It is known that the two Romanian Churches in Transylvania contributed over time to the loyalty of the Transylvanian Romanians to the House of Habsburg. Maintaining this high loyalty towards the Vienna Court was all the more necessary during the war when the Romanians, together with the other peoples of the Empire, had to prove their attachment to the homeland and to the Throne. The present study analyzes the attitude that the hierarchies of the two Romanian Churches in Transylvania had at the time of the outburst of the war and during its unfolding, with the emphasis on the messages transmitted to the pastors to maintain the enthusiasm of war. It shall not overlook the recommendations of the high prelates regarding the spouses' fidelity, social morality, the care for widows and war orphans, or the strategies concerning new wartime pastoral that amplified the religious sentiment, causing a rediscovery of perennial Christian values. Rezumat: Loialism dinastic, moralitate şi valori familiale la românii din Transilvania în timpul Primului Război Mondial. Este cunoscut faptul că cele două Biserici româneşti din Transilvania au contribuit de-a lungul timpului la loializarea românilor ardeleni faţă de Casa de Habsburg. Menţinerea la cote ridicate a acestei fidelizări faţă de Curtea de la Viena a fost cu atât mai necesară în timpul războiului, când românii, alături de celelalte popoare din Imperiu, au trebuit să dea dovada ataşamentului faţă de patrie şi Tron. Prezentul studiu analizează atitudinea pe care ierarhiile celor două Biserici româneşti din Transilvania au avut-o în momentul declanşării războiului şi de-a lungul desfăşurării lui, accentul fiind pus asupra mesajelor transmise păstoriţilor pentru a întreţine entuziasmul de război. Nu vor fi trecute cu vederea recomandările înalţilor prelaţi în ceea ce priveşte fidelitatea soţilor, morala socială, grija faţă de văduve şi orfanii de război sau strategiile privind noua pastoraţie adaptată contextului războiului, care a amplificat sentimentul religios, determinând o redescoperire a valorilor creștine perene. Cuvinte-cheie: mesaje, Biserică, Transilvania, loialism, familie, morală.